2016
DOI: 10.1038/cdd.2016.80
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy requires poly(adp-ribosyl)ation-dependent AMPK nuclear export

Abstract: AMPK is a central energy sensor linking extracellular milieu fluctuations with the autophagic machinery. In the current study we uncover that Poly(ADP-ribosyl)ation (PARylation), a post-translational modification (PTM) of proteins, accounts for the spatial and temporal regulation of autophagy by modulating AMPK subcellular localisation and activation. More particularly, we show that the minority AMPK pool needs to be exported to the cytosol in a PARylation-dependent manner for optimal induction of autophagy, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 34 publications
2
39
1
Order By: Relevance
“…PARP inhibition resulted in enhanced autophagosome formation and higher LC3B protein level. The role of PARP1 in the regulation of autophagy is still poorly understood, both autophagy inducer [70] and inhibitory effect of PARP1 [75] can be found in the literature. In our model system, increased autophagosome formation after UVB and PARPi can be attributed to the elevated level of DNA damage (higher CPD content), which serves as a positive signal for autophagy since the initiation of global genome NER (GG-NER) subpathway is controlled by autophagy [67,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PARP inhibition resulted in enhanced autophagosome formation and higher LC3B protein level. The role of PARP1 in the regulation of autophagy is still poorly understood, both autophagy inducer [70] and inhibitory effect of PARP1 [75] can be found in the literature. In our model system, increased autophagosome formation after UVB and PARPi can be attributed to the elevated level of DNA damage (higher CPD content), which serves as a positive signal for autophagy since the initiation of global genome NER (GG-NER) subpathway is controlled by autophagy [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the role of PARP1 in the regulation of autophagy is controversial. Both autophagy inductor [70][71][72] and inhibitor [73][74][75] role of PARP1 has been described suggesting that the autophagy-modulatory effect of PARylation might show DNA damage and cell type specificity. Even though, we detected an increased number of LC3 puncta, this type of macroautophagy cannot be considered as mitophagy since autophagic puncta show very mild colocalization with mitochondria ( Figure 5D).…”
Section: Parp Inhibition and Uvb Induces Bulk Autophagy But Not Mitopmentioning
confidence: 99%
“…Previous reports showed that activated PARP1 can induce mitochondrial dysfunction and modify α‐synuclein into more toxic strains, accelerating the pathological progress of PD (Kam et al., 2018). In addition, PARP1 also interacts with AMPK (Rodriguez‐Vargas et al., 2016). AMPK is a key molecule in bioenergy metabolism and participates in the activation of autophagy during cell starvation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to DNA damage, nutrient deprivation can be considered as the most physiological stimulus to induce reversible autophagy. Recent studies of our group have implicated PARP-1 in autophagy induced by nutrient starvation [115,121]. The absence of PARP-1 or the use of PARP inhibitors (PJ34, DPQ and Olaparib) delay starvation-induced autophagy.…”
Section: Parylation In Autophagymentioning
confidence: 99%
“…The absence of PARP-1 compromises the activation of AMPk, more precisely the isoform AMPkα, reducing phosphorylation on Thr172 [121,122]. A nuclear subpopulation of AMPkα was detected in the breast cancer cell line MCF7, where it forms a stable complex with PARP-1; moreover the activation of nuclear AMPkα requires two essential events: Firstly, starvation-induced ROS must be imported to the nucleus to generate DNA damage and PARP-1 activation.…”
Section: Parylation In Autophagymentioning
confidence: 99%